Reciprocal-relationship between the development of "Trans Jogja" public transportation and urban spatial structure in Yogyakarta agglomeration - Ashari, Arif; Olivia, Raisya A.; Reswari, Az-Zahra A.; Brotowiranti, Rayung W.; Hadi, Bambang S.; Ervin, Muhamad (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2024)
Transportation activities cannot be separated from the spatial structure of a region. Local spatial structure applies to areas characterized by urban-hinterland systems with modest coverage, such as Yogyakarta. In this paper, we evaluate the reciprocal relationship between the development of public transportation "Trans Jogja" and the urban spatial structure in Yogyakarta City and its satellite areas. The data collected are secondary data obtained from documentation and primary data from observation, including Trans Jogja routes and bus stops, location of population activity centers, land use, and population data. Data analysis was conducted using GIS analysis using average nearest neighbor, buffering, and overlay; statistical analysis using simple linear regression; and descriptive analysis. There are two main findings in this study. First, transportation services develop following the characteristics of population activities, as evidenced by the distribution pattern of routes and bus stops that follow the location of activity centers and population density. Second, transportation development also triggers the formation of urban landscapes that tend to exurbanize. In summary, this study offers alternative information that provides new insights into the reciprocal relationship between transportation development and the spatial structure of cities in Indonesia.